Analyzing Teachers’ Praise In Classroom Interaction - Afrillia Anggreni; Hastini Hastini; Erniwati Erniwati (Institut Agama Islam Negeri Palopo, 2019)
This is qualitative research that applied discourse analysis method. The objectives of this research are to clarify (1) the dominant praise used by the English teachers in the classroom interaction and (2) the function of praise given by the English teachers in the classroom interaction. The informants of this research were two students of English Education Study Program who took Pengenalan Lingkungan Persekolahan Program (PLP).The data were collected by using audio recording and note observation. The results of the research show that (1) the teachers dominantly use okay and good in giving Praise and (2) the functions of the praise are given by both of teachers as: to construct the good communication, to support positive learning behavior, to reward good students conduct and achievement and to express approval, admiration and delight during the teaching-learning process. The result also shows that both of teachers still have limited expression in giving praise.